Top earners and earnings inequality during the COVID-19 pandemic: Evidence from Ecuadorian administrative data - Olivier Bargain; Paul Carrillo-Maldonado; H. Xavier Jara (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper aims to assess the extent to which top earners in Ecuador were affected by the COVID-19 crisis compared to other segments of the population. Our analysis uses administrative data for individuals affiliated to social security between January 2019 and December 2021. We identify the top 10, 1, and 0.1 per cent of earners in 2019 and analyse changes in their monthly earnings during the pandemic compared to those of the rest of the registered workforce. Our analysis shows that the only group that experienced a recovery in employment was workers who were not at the top of the pre-pandemic earnings distribution. Conditional on being in registered employment, mean earnings also dropped in the second quarter of 2020 across all earning groups (top and non-top). By the end of 2021, earnings had recovered for non-top earners and the top 10 per cent group. However, earnings remained below pre-pandemic levels in the top 1 per cent and top 0.1 per cent groups. Finally, earning disparities across population subgroups substantially increased among individuals who were not at the top of the earnings distribution.
Keywords: D13; H12; H24; J22; 330; top earners; employment; earning disparities; COVID-19; administrative data